Experimental investigation of broadband thrust and loading noise from pumpjet due to turbulence ingestion. (1st July 2022) - Xiong, Ziying; Rui, Wei; Lu, Linzhang; Zhang, Guoping; Huang, Xun
Abstract: Noise emitted from a rotor due to its interaction with ingested turbulence is dominant for modern submarine propulsors. An experimental study of broadband thrust from a couple of representative pumpjet configurations is conducted in this work. The associated loading noise is further predicted by incorporating the Ffowcs Williams–Hawkings acoustic analogy, which enables the projection of the local unsteady thrust measurements to the far-field noise predictions. Both the unsteady thrust measurements and the loading noise predictions are validated by comparing to the asymptotic relations from acoustic analogy and the Blake's spectral method, respectively. The good agreement justifies the manipulations, such as the far-field dipole approximation and compact source assumption for the pumpjet, which have been adopted for the current problem set-up. Moreover, the spectra of the unsteady thrust and the loading noise are characterized by the haystacking phenomenon around the blade passing frequencies, where the tonal peaks are broadened due to the ingestion of turbulent structures. Overall, the experimental results given in this paper should be helpful in extending the noise testing capability of the current experimental facilities, as well as in deepening the understanding of the inherent fluid mechanism relevant to haystacking phenomenon and will eventually benefit low-noise pumpjet designs. Highlights: This work has conducted the experimental study of broadband unsteady thrust and predicted the corresponding noise from representative pumpjet configurations. All the relevant design details are disclosed to be a baseline problem. Our findings show the spectra of the unsteady thrust and the loading noise are characterized by the haystacking phenomenon, which should deep our physical understanding and benefit low-noise pumpjet designs. The unsteady thrust has been projected to the far-field loading noise. The approach has been carefully validated, which help to extend the noise testing capability of the current experimental facilities, from hydrodynamics to hydroacoustics.